Overview of Depression in The Elderly of UPT Pelayanan Sosial - Relang Rizky Mulyadi; Alif Mardijana; Yudha Nurdian (Faculty of Medicine, University of Jember, 2016)
Depression is a prolonged sadness and a feeling or abnormal. Can be used to demonstrate a variety of phenomena, such as signs, symptoms, syndrome, emotional, reaction. Depression is more common in older people than depression in the general population with a prevalence rate of 25-50%. Elderly according to article 1, paragraph (2), (3), (4) of Law No. 13 of 1998 on the health of the elderly is said that a person who has reached the age of 60 years. The purpose of this study to determine the incidence and the general picture of depression that occurs at the level of the elderly who live in UPT Pelayanan Sosial Lanjut Usia Kabupaten Jember. This study is observational analytic cross sectional design. The variables observed in this study is the age and level of depression. Respondent has been investigated by using the GDS (Geriatric Depression Scale). Population in this study was all elderly that live in UPT Pelayanan Sosial Lanjut Usia Jember as much as 43 respondents. Spearman Rho analysis showed significance level 2.57 which shows 2.57> 0.05 p. This means that there is no significant relationship between age of elderly with depression levels among respondents in UPT Pelayanan Sosial Lanjut Usia Kabupaten Jember. Key words: Depression, Elderly.